2018 Kansas Performance Tests with Winter Wheat Varieties - Roozeboom, Kraig; Lingenfelser, Jane; Davis, Holly; De Wolf, Erick; Fritz, Allan; Knapp, Mary; Lollato, Romulo; Regan, Rebecca; Whitworth, Jeff (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2018)
The Kansas Agricultural Experiment Station annually compares both new and currently grown varieties in the state’s major crop-producing areas. These performance tests generate unbiased performance information designed to help Kansas growers select wheat varieties suited for their area and conditions.
Keywords: Wheat; Crop development; Diseases; Weather; Insects; Statistics; Kansas